Investigation of the Effectiveness of the Research Skills Teaching Program - Omer Kutlu; Betül Polat (International Journal of Assessment Tools in Education, 2022)
In this study, it was investigated whether the Research Skills Teaching Program (RSTP) prepared for elementary school 4th grade students was effective in imparting the sub-skills required for conducting the research process to students. To this end, pretest-posttest control group design; one of the quasi-experimental designs; was employed. The study was conducted on the students attending two classes of a state elementary school. In the experimental group, the program developed on the basis of the Big Six Research Skills Model was administered, while no such special application was conducted in the control group. In both of the groups, the Research Skills Test was administered as pretest and posttest and Monitoring Tests. The collected data were analyzed by using Independent Samples t-test and Paired Samples t-test. The responses given by the experimental and control group students to each of the open-ended items in the Monitoring Tests were separately examined. It was found that the activities developed within the context of the teaching program had comprehensive effect on the development of the skills needed to direct the research process. When the number of the students giving the most correct answers in the items in the monitoring tests was examined, it was seen that although there are students finding the most correct answers to the items in the experimental group, their levels of using these strategies were not found to be at the desired level and there are students in the control group finding the most correct answers only for four skills.